INOVASI PERTANIAN DAN ADOPSINYA OLEH PETANI JAGUNG DI KECAMATAN SUWAWA SELATAN PROVINSI GORONTALO - Raisha Candrika Fatima Diko; Mahludin Baruwadi; Zulham Sirajuddin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Sustainable agricultural development in rural areas is an issue of strategic importance that has been of concern and discussion lately. Therefore, this study aims to identify the adoption rate of maize farmers of sustainable agricultural practices in East Bulontala Village and Libungo Village. This research is descriptive and uses quantitative methods, where the data is primary. The results of the statistical test were used to compare the adoption rate of maize farmers in East Bulontala Village and Libungo Village. The results showed that corn farmers' knowledge level in the South Suwawa District, especially in East Bulontala Village and Libungo Village about sustainable agricultural practices, was still relatively low. However, the adoption rate of farmers in East Bulontala Village is still greater than that of farmers in Libungo. Therefore, increasing knowledge of sustainable agricultural practices in these two villages needs to be carried out, especially in the components of reducing pesticide use, intercropping behavior, and tree planting behavior.